2020
DOI: 10.15826/recon.2020.6.4.020
|View full text |Cite
|
Sign up to set email alerts
|

The causal relationship between agricultural production, economic growth, and energy consumption in Ghana

Abstract: Relevance. Transition to a low-carbon economy in order to effectively and efficiently exploit the natural resource base of a country is a daunting task, especially for developing countries due to their over-reliance on climate factors. This study focuses on the case of Ghana and assesses the impact of several indicators – agricultural production, economic growth and energy consumption – on the environment. Research objectives. The aim of the study is to describe the causal relationship between agriculture pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
3
6
0
Order By: Relevance
“…This result means that a 1% increase in AEC causes a 0.08% decrease in agricultural greenhouse gas emissions, in the long run, other variables being constant. These results are in line with the results of Appiah et al (2018) and Chandio et al (2020), but it differs from that of Ben Jebli and Ben Joussef (2017), Liu et al (2017), Agboola and Bekun (2019), Ali et al (2020) and Koshta et al (2020). Studies examining the relationship between energy consumption and CO 2 emissions have mostly found that energy consumption increases CO 2 emissions.…”
Section: Diagnostic Tests For Ardl Modelssupporting
confidence: 85%
See 3 more Smart Citations
“…This result means that a 1% increase in AEC causes a 0.08% decrease in agricultural greenhouse gas emissions, in the long run, other variables being constant. These results are in line with the results of Appiah et al (2018) and Chandio et al (2020), but it differs from that of Ben Jebli and Ben Joussef (2017), Liu et al (2017), Agboola and Bekun (2019), Ali et al (2020) and Koshta et al (2020). Studies examining the relationship between energy consumption and CO 2 emissions have mostly found that energy consumption increases CO 2 emissions.…”
Section: Diagnostic Tests For Ardl Modelssupporting
confidence: 85%
“…The crop production index (CPI) has a positive and statistically significant effect on agricultural emissions, and this result implies a 1% increase in the CPI increases agricultural emissions by 0.37%. This result is supported by Sarkodie and Owusu (2017), Appiah et al (2018), Ali et al (2020), Chandio et al (2020), and Leitao and Balogh (2020). The incorrect tillage, irrigation methods, overuse of chemical fertilizers, and pesticides increase the negative effects of crop production on the environment.…”
Section: Diagnostic Tests For Ardl Modelsmentioning
confidence: 84%
See 2 more Smart Citations
“…In another study, Ali and Amfo (2021) compared the economic and ecological values of selected countries from 1960 to 2018 and concluded that renewable energy consumption leads to a decrease in carbon emissions. Finally, Ali and Anufriev (2020) explored the causal relationship between fossil fuels and emissions in Ghana using data from 1975 to 2014 and found that fossil fuels exacerbate carbon emissions.…”
Section: Literature Reviewmentioning
confidence: 99%